PERMASALAHAN DAN STRATEGI PENCAPAIAN PROVINSI LAYAK ANAK, STUDI KASUS DI PROVINSI ACEH - Desy Maritha; Husniati Uty (Jurnal Transformasi Administrasi, 2022)
This study aims to formulate several strategies related to the steps of the Aceh provincial government in achieving one of the national priorities, namely child-friendly city. According to the regulation of the Minister of Women's Empowerment and Child Protection number 11 Year 2011, that achieving the title of Child Friendly City must meet thirty one (31) indicators of Fulfillment of Children's Rights, which consists of 6 parts, namely institutional strengthening, and five (5) child rights clusters. , namely: civil rights and liberties cluster, family environment and alternative care cluster, basic health and welfare cluster; education, leisure and cultural activity clusters; and special protection clusters. The research method in this research is descriptive qualitative method, using a combination of primary and secondary data. Primary data was obtained through interviews, focus group discussions with relevant agencies, and secondary data sourced from several studies of applicable laws and regional regulations (Qanun of Aceh Province), as well as several regulations and other documentation related to the indicators that must be achieved. This study also provides several conclusions and suggestions that become policy recommendations for achieving Child Friendly Cities (KLA) in Aceh Province